The Effect of Scopolamine on Avoidance Memory and Hippocampal Neurons in Male Wistar Rats - Saba Seifhosseini; Mehrdad Jahanshahi; Ali Moghimi; Nasrin-Sadat Aazami (Basic and Clinical Neuroscience, 2011)
Introduction: Cholinergic systems are involved in learning and memory. Scopolamine, a muscarinic acetylcholine receptor antagonist, is used as a standard/ reference drug for inducing cognitive deficits in healthy humans and animals. The purpose of this study was to evaluate the effects of scopolamine on avoidance memory and number of neurons in rat’s hippocampus. . Methods: Thirty five male albino Wistar rats (200 ± 20 g) were used in this study. The rats were divided randomly into five groups: control group (healthy samples), sham (saline) and 3 experimental groups 0.2, 0.5 and 1 mg/kg (intraperitoneally - single dose of Scopolamine). Animals were tested by passive avoidance method (shuttle box). After one week, a memory test was taken from rats. Finally, with dissection of the rats' brains and tissue operations, neurons were stained with cresyl violet. Photographs of the samples in hippocampal areas were prepared, and neurons were counted. Results: Our results showed that the number of neurons in all experimental groups was lower than that in the control group. The highest decrease in number of neurons was shown in response to 1 mg/kg scopolamine compared to the control group in all regions of hippocampus. Also, we found that in comparison to the saline-treated animals, the injection of scopolamine to rats after training, caused memory destruction. Discussion: We concluded that memory impairment-induced by scopolamine is probably associated with neuronal loss and this decrease was dose dependent.